Cultural Constraints in Subtitling and Dubbing Arabic Series into English: A Case Study of the Saudi Series “Alkhallat” - Alkhatib, Ruba; Ahmad S Haider; AlKhatib, Laith (Forum for Linguistic Studies, 2024)
Dubbing and subtitling foreign movies, series, and other audiovisual products have flourished since the invasion of the screens; hence, the translation task between languages and cultures became integral to cope with this vast expansion. The different cultural and religious backgrounds of Arabic and English-speaking cultures complicate the translation of Arabic television series. Therefore, translators should be multicultural and multilingual, especially when working between Western and Eastern cultures. The current study aims to investigate the strategies used by Netflix professional translators to ensure the ideas are culturally conveyed effectively to the intended audience. The research compared the English subtitled and dubbed versions of the Arabic-Saudi series Alkhallat with the original version screened on Netflix. The findings showed that the main subtitling and dubbing strategies that were used were cultural substitution, omission, and paraphrasing. The findings also showed that although the dubbed and subtitled versions employed similar strategies, the wording varied. This variation could be attributed to the differences between spoken and written modes. The current study concludes that translators must understand the source and target cultures and consider the constraints of each AVT mode in order to provide a good quality translation.